Distribución espacial de Trichocereus pasacana (Cactaceae) en relación al espacio disponible y al banco de semillas - de Viana, Marta Leonor (1996)
Pattern of Trichocereus pasacana was studied in relation to both the available spaee and the seed bank, in two sites: Cardonal and Duendeyacu at Los Cardones National Park (Salta, Argentina); 96% of the cactii were associated with other shrub species. Association levels were not correlated with plant height.There were more individuals than would be expected by chance under the canopy of Larrea divaricata, Aphyllocladus spartioides and Prosopis ferox.The seeds in the.bank were more abundant than expected under the canopy of Baccharis boliviensis, Verbena sp, Prosopis ferox, Aphyllocladus spartioides and Senna cressiramea, a result that is partially correlated with the observed in the population.